Impact of Forgiveness Therapy on the Self-Esteem of Working Women Exposed to Spousal Emotional Abuse in Lagos Metropolis, Nigeria - SORIYAN, Tiwalade Olubukola; ADENIYI, Samuel Olufemi; ANYAMA, Stella Chinwe (Ilorin Journal of Education, 2024)
Spousal emotional abuse is a deeply distressing and pervasive issue, exacting a profound toll on the self-esteem of working women exposed to it. These adverse effects encompass a range of emotional, psychological, and social challenges which make life burdensome for the victims. Therefore, this study examined the impact of forgiveness therapy on the self-esteem of working women who have endured emotional abuse within their spousal relationships in Lagos Metropolis, Nigeria. Quasi-experimental pre-test/post-test control group design was adopted. A sample of 23 participants, comprising 12 wage and 11 self -employed women was selected for the study using purposive sampling processes. Two instruments used to collect relevant data were the Profile of Psychological Abuse of Women by Sackett and Rosenberg Self Esteem Scale (RSE) with reliability indexes of 0.91 and 0.77 respectively. A researcher designed questionnaire was employed to capture the biodata of respondents such as age group, employment type, marital status. The hypotheses were tested using two-way analysis of variance (ANOVA) and the analysis of covariance (ANCOVA) at 0.05 level of significance. The study revealed that participants’ levels of self-esteem were significantly different when exposed to Forgiveness Therapy. It was also discovered that employment type was a significant factor on self-esteem when the therapy was applied. Hence, one of the recommendations is that Forgiveness Therapy should be employed to improve self-esteem among working women with emotionally abusive spouses.